ZONEAMENTO URBANO COMO INSTRUMENTO DE DEMARCAÇÃO DE ZEIS: UMA ANÁLISE NO MUNICÍPIO DE IPATINGA - MG - Oliveira, Vivian; Abreu, Renan; Lisbanho, Rafael (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Special Social Interest Zones - SSIZ are defined areas in the macrozoneamento of the cities with the objective of guaranteeing access to decent housing. However, the location of the SSIZ in most cities can configure a vector of urban expansion, being located in the most peripheral areas and with lower supply of basic infrastructure. The present article aims to present and discuss the location of the SSIZ areas in the city of Ipatinga - MG. To that end, all the areas destined to SSIZ by the Master Plan of the city were identified and the characteristics of each of them were identified in relation to its location in the urban land, its surroundings and the existing services. We analyzed the empty SSIZ that were destined exclusively or exclusively for Housing of Social Interest. Thus, it was possible to identify that the municipal urban planning, having as main instrument the urban zone, sectoralized the SSIZ in areas that are configured as a vector of urban expansion, without adequate minimum infrastructure, close to the municipality's border with the public jail and in areas with restricted access. SSIZ should guarantee quality of life for its population and all the services existing in the city in an equalized way.